(untitled) (Revista Contexto & Saúde, 2026)
Objective: To contribute, through health education, to a safe hospital discharge for adolescents diagnosed with Diabetes Mellitus. Method: Action research was employed as the research method, conducted with the target population of adolescents with Diabetes Mellitus. The study setting was a public hospital in the Federal District, Brazil, and it was carried out between October 2022 and May 2023. Health technology tools were used, including a Comic Book, a Memory Game, and a Standard Operating Procedure, which were presented to the adolescent and a family member during a health education session supported by therapeutic play. Participant observation was conducted using a field diary, along with a questionnaire to collect the adolescent’s sociodemographic and clinical data. The narrative description of the analysis was developed in light of the theoretical framework. Results: The technological tools were identified as useful and appropriate during the session with a 13-year-old adolescent living in the Federal District, accompanied by her mother. The tools were well accepted, and learning was strengthened, contributing to a safer hospital discharge process. Conclusion: The intervention expanded the range of options available to health professionals, focusing on the implementation of safe discharge practices and the use of care tools directed at the target population, with the potential to broaden their applicability to other age groups and study settings.